AFFIXIATION IN LANGUAGE LEARNING AND WORD FORMATION - Turaxonova Marjona,; Yóldosheva Marjona,; Norkobilov Quddus, (TADQIQOTLAR, 2026)
Annotation This article explores the concept of affixiation as a key process in morphology and its significant role in language learning. Affixiation involves adding prefixes and suffixes to base words in order to create new lexical items and grammatical forms. The paper analyzes how mastering affixiation enhances vocabulary acquisition, improves reading comprehension, and supports learners in developing accurate language use. Furthermore, the study highlights effective classroom strategies for teaching affixiation and demonstrates its importance in building independent and confident language users.